2014
DOI: 10.1089/acm.2013.0176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thai Traditional Massage on Pressure Pain Threshold and Headache Intensity in Patients with Chronic Tension-Type and Migraine Headaches

Abstract: TTM could increase PPT and reduce headache intensity, suggesting that this is a possible alternative treatment for chronic headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 25 publications
7
28
0
Order By: Relevance
“…In the RCT ran by Chatchawan et al [20], the effects of Pairwise comparisons showed that head pain, measured by numerical pain rating scale, decreased 24 hours after manual therapy (p < 0.05) but not after the placebo intervention (p = 0.9). On the other hand, no signifi cant changes were found in PPT levels (right F = 0.3, p = 0.6, left F = 0.4, p =0.5).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the RCT ran by Chatchawan et al [20], the effects of Pairwise comparisons showed that head pain, measured by numerical pain rating scale, decreased 24 hours after manual therapy (p < 0.05) but not after the placebo intervention (p = 0.9). On the other hand, no signifi cant changes were found in PPT levels (right F = 0.3, p = 0.6, left F = 0.4, p =0.5).…”
Section: Resultsmentioning
confidence: 98%
“…This review, evaluating the effi ciency of soft tissue therapy for patients with TTH, has included eleven studies. The soft tissue techniques used in the studies were massage and soft tissue mobilization [16][17][18][19][20]22,25], suboccipital soft tissue inhibition [23,24], and direct technique myofascial release [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided the evidence for a combined approach of acupuncture and stretching, and it was fundamental for the approach selected in this study (Wilke et al, 2014). Physiotherapy and hands-on techniques have also showed promising results in TTH, as earlier and recent research (Bevilaqua-Grossi et al, 2016;Bodes-Pardo et al, 2013;Chatchawan et al, 2014;Moraska et al, 2015) has shown. Either as monotherapies or as combinations, positive therapeutic results have been described in the review by Espi-Lopez et al…”
Section: Ppt Measurementsmentioning
confidence: 89%
“…Myofascial release techniques aim to treat the sensitized myofascial trigger points and fascia and the referred pain patterns they produce, providing a direct connection with TTH clinical image and patient's subjective pain experience (Alonso‐Blanco, de‐la‐Llave‐Rincon, & Fernandez‐de‐las‐Penas, ). It is also evidenced that interventions aiming at the fascia (Chatchawan, Eungpinichpong, Sooktho, Tiamkao, & Yamauchi, ) and myofascial trigger points manage to reduce the local headache pain intensity, the extent of referred pain fields, and the pressure pain sensitivity (Toro‐Velasco, Arroyo‐Morales, Fernandez‐de‐Las‐Penas, Cleland, & Barrero‐Hernandez, ).…”
Section: Introductionmentioning
confidence: 99%
“…In both groups headache intensity and frequency were improved over baseline but were not different from each other. 39 An open RCT in 29 people with chronic pain, including headache, compared classic massage (10 sessions of 20 minute massage over five weeks) to standard medical care. It found no significant difference in pain after treatment but at three months' follow-up people who had massage had persistent pain reduction compared with controls (P=0.003; no absolute numbers provided).…”
Section: Safetymentioning
confidence: 99%